The Impact of Restrictions in Trade in the Telecommunications: an Application to Middle East and North African Countries - (:unkn) unknown (My University, 2012)
Theoretically, welfare gains from liberalisation of trade in services arise from falling prices and technology transfers from foreign firms. Empirically, due to the role of the regulatory framework in barriers to trade in services ('behind-the-border' laws) substantial gains are only reached when entry of foreign firms is widened. We have a close look at the way impediments to trade in services affect cost-price margin in telecommunication in Middle East and North Africa (MENA) countries. First, we criticise the measurements of barriers in trade in services, which tend towards an overestimation. Second, we show that analyses bend to overvalue the impact of regulations on the cost-price margin in telecommunications for MENA countries, in line with inadequate econometric techniques or underestimation of the effect of technical progress. Therefore, the best way in terms of trade in services liberalisation is to opt for a flexible, qualitative interpretation of the quantitative results and rank ordering of countries.
Keywords: African Research